Formal Methods for Components and Objects 5th International Symposium, FMCO 2006, Amsterdam, Netherlands, November 7-10,2006, Revised Lectures - de Boer, Frank S.; Bonsangue, Marcello M.; Graf, Susanne; de Roever, Willem-Paul (Programming and Software Engineering,, 2007)
Formal methods have been applied successfully to the verification of medium-sized programs in protocol and hardware design. However, their application to the development of large systems requires more emphasis on specification, modelling and validation techniques supporting the concepts of reusability and modifiability, and their implementation in new extensions of existing programming languages. This book presents 12 revised lectures given by top-researchers at the 5th International Symposium on Formal Methods for Components and Objects, FMCO 2006, held in Amsterdam, Netherlands, in November 2006. The book provides a unique combination of ideas on software engineering and formal methods that reflect the current interest in the application or development of formal methods for large scale software systems such as component-based systems and object systems. The papers are organized in topical sections on component and service oriented computing, system design, tools, algebraic methods, model checking, assertional methods, and quantitative analysis.